Impacts of irrigation heterogeneity on sugarcane yields, energy and water use in sub-saharan Africa. - Banda, Mavuto Muhammad (Cranfield University, 2023)
Sugarcane is an economically strategic crop in Sub-Saharan Africa (SSA), underpinning the rural livelihoods and economies of many SSA countries. Despite its economic importance, yield trends in the region have been declining by an average of 0.03 t/ha per year over the last 60 years. However, total cane production has been increasing by an average of one million tonnes per year over the same period – an indication that the increase in total cane production has largely been due to an overall expansion in cultivated area. However, this situation is not sustainable in the long-term since land availability is limited. Whilst irrigation has the potential to improve yields, production in SSA is typically characterised by poor irrigation management practices as evidenced by high levels of irrigation water use, low irrigated yields and low water productivities. Understanding the impacts of future climate variability and drought risk on the reliability of irrigation and identifying appropriate technology and management options to improve yields, water and energy use and productivity are key challenges facing the agricultural sector in SSA. Impacts of irrigation non- uniformity on cane yields, water and energy use in SSA were identified as key research gaps in this study. Thus, the aim of this research was to evaluate the agronomic, environmental and economic impacts of irrigation non-uniformity on sugarcane production in SSA. Initially, a benchmarking study was conducted to identify opportunities to improve cane yields and water productivity and reduce irrigation water and energy use. Biophysical crop, water balance and economic modelling approaches were then integrated to simulate cane yield response to water, the impacts of irrigation non- uniformity and the relative cost and benefits of improving irrigation uniformity. Cane yields were modelled for varying water applications and irrigation uniformity using the DSSAT Canegro model coupled with a water balance model. The relative financial costs and benefits of implementing different interventions to improve irrigation management were then evaluated using a spreadsheet-based economic model. The results showed that there were opportunities to improve the performance of irrigated cane production in SSA – currently characterised by lower-than- expected yields – ranging between 83.9 and 108.9 t/ha, high irrigation water uses and lower than potential water productivity – ranging between 5.0 and 7.8 kg/m³. It was also established that improving irrigation uniformity leads to improved cane yields, reduced irrigation water and energy use. It was also established that on average a percentage improvement in irrigation uniformity could improve yields by 0.2 – 0.5 t/ha and could reduce irrigation and energy use by 3%. These potential yield improvements (due to improved irrigation uniformity) coupled with a reduction in water and energy use resulted in increased revenues of between 23,300 and 70,900 MK/ha (c£18 – 65/ha) and a reduction in irrigation-related costs by 3,700 MK/ha (c £3/ha). Overall, the research has provided new valuable insights into the impacts of irrigation heterogeneity on cane yields and addressed existing knowledge gaps relating to how existing irrigation management practices in the sugarcane industry in SSA can be improved, without the need for transformational shifts to precision irrigation technologies. The findings provide the basis for improving cane yields, irrigation water and energy use and productivity in both commercial and smallholder cane production across SSA. It is, thus, recommended that there is a need for farmers to always operate irrigation with improved level of irrigation uniformity while ensuring proper irrigation scheduling approaches. The implementation of irrigation uniformity improvement interventions and adopting correct irrigation scheduling methods would likely reduce irrigation water use, improve yield average at field level which in turn will improve water productivity and reduce energy requirements for irrigation. The improvement of water productivity and reduction of irrigation water use and energy requirements would maximise crop yield benefits from irrigation and reduce irrigation operation costs, respectively.
Hess, Tim M. - Associate Supervisor
Keywords: Benchmarking; crop modelling; DSSAT Canegro; irrigation uniformity; water use reduction; yield increase